2014
DOI: 10.5005/jp-journals-10024-1556
|View full text |Cite
|
Sign up to set email alerts
|

Apical Extrusion of Debris and Irrigant using Novel Preparation Systems

Abstract: Aim:The aim of this in vitro study was to assess the amount of apically extruded debris and irrigant using Reciproc vs self-adjusting file (SAF) and to investigate the effect, if any, of gravitational force via mandibular and maxillary positioning of the teeth. Materials and methods:Forty human mandibular premolars were randomly assigned to four groups of 10 teeth each. The root canals were instrumented according to the manufacturers' instructions using the Reciproc and SAF. Sodium hypochlorite was used as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…On the other hand, when the location of the tooth was considered as the primary variable irrespective of the tested instruments, significantly more debris extrusion was observed for mandibular teeth. This finding is consistent with the results published by Uzunoğlu & Görduysus (), who reported the same observation during primary root canal treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, when the location of the tooth was considered as the primary variable irrespective of the tested instruments, significantly more debris extrusion was observed for mandibular teeth. This finding is consistent with the results published by Uzunoğlu & Görduysus (), who reported the same observation during primary root canal treatment.…”
Section: Discussionsupporting
confidence: 93%
“…, Bürklein et al . ) and it has been suggested that gravity may play a role both in access of the irrigants to the apical foramen and their extrusion beyond the canal terminus (Uzunoğlu & Görduysus ). The impact of gravity on debris extrusion during retreatment procedures in severely curved root canals has not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been various studies showing the efficacy of SAF in reducing the amount of apical debris extrusion. It has been compared with ProTaper Universal, ProTaper Next, and WaveOne,[ 14 15 ] with Reciproc[ 16 ] wherein the findings of our study are in agreement.…”
Section: Discussionsupporting
confidence: 76%
“…18 Distilled water though not the preferred root canal irrigant was used during the retreatment procedure because the use of saline or sodium hypochlorite may have a positive effect on the weight of debris extruded. 19 No attempt was made to simulate the periapical tissues as the floral foam used may absorb the extruded irrigant and debris and interfere with the results. 7 The Myers and Montgomery model is the most widely accepted and commonly used system for assessing the apically extruded debris and was thus used in this study.…”
Section: Discussionmentioning
confidence: 99%